(untitled) (Bangladesh Journal of Microbiology, 2016)
Earlier observation of cellular damage of Pseudomonas aeruginosa (SUBP01) by the extrinsic oxidative agent (H2O2) and the assumptive accumulation of the reactive oxygen species (ROS) through aeration further led to the growth retrieval assay of the bacterium. Current study investigated the influence of the inorganic growth stabilizers (20 mM MgSO4 plus 5 mM ethylenediaminetetraacetic acid, EDTA) and the organic extracellular fractions of the heat-resistant Bacillus species (SUBB01) and P. fluorescens (SUBP02) on the growth pattern of P. aeruginosa at 45° and 46°C. Bacterial growth (cfu) was measured on the minimal agar plates up to 72 hours, microscopic experiments to monitor the subsequent morphological changes, and finally by the spot tests to examine the cell viability under the given heat stressed conditions. As expected, growth revival was observed at both 45° and 46°C after 48 to 72 hours, upon supplementation with inorganic growth stabilizing agents and the extracellular fractions (secretions) of P. fluorescens compared to that of the control; i.e., untreated with inorganic or organic supplements. Interestingly, compared to that of P. fluorescens extracellular extracts, no positive impact on growth retrieval was noticed by the application of the extracellular fractions of Bacillus species. Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 59-64